2015
DOI: 10.1136/vr.102546
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for survival in dogs with pituitary‐dependent hypercortisolism treated with trilostane

Abstract: Pituitary-dependent hypercortisolism (PDH) is one of the most frequent endocrinopathies in dogs, but prognostic factors are largely unknown. The aim of this retrospective case series study was to determine the prognostic value of different clinical and clinicopathological variables evaluated in dogs newly diagnosed with PDH that were subsequently treated with trilostane. Medical records from one referral centre were evaluated. Eighty-five dogs with PDH were included. The median survival time was 852 days (rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
52
3
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(67 citation statements)
references
References 30 publications
8
52
3
4
Order By: Relevance
“…In our study, plasma phosphate concentration was not available for most dogs and could not be investigated as a prognostic factor. In a previous study, pre‐ACTH cortisol was not found to be associated with survival time in dogs with PDH treated using trilostane . However, in untreated cases, excess cortisol may be related to survival time, considering that the high mortality rate of Cushing's syndrome in humans may be associated with the effects of excess cortisol .…”
Section: Discussionmentioning
confidence: 84%
“…In our study, plasma phosphate concentration was not available for most dogs and could not be investigated as a prognostic factor. In a previous study, pre‐ACTH cortisol was not found to be associated with survival time in dogs with PDH treated using trilostane . However, in untreated cases, excess cortisol may be related to survival time, considering that the high mortality rate of Cushing's syndrome in humans may be associated with the effects of excess cortisol .…”
Section: Discussionmentioning
confidence: 84%
“…The main prognostic factors for long‐term remission in dogs were pituitary gland size, thickness of the sphenoid bone, plasma α‐melanocyte stimulating hormone (α‐MSH) concentration, and urinary cortisol excretion before surgery . Recently, the long‐term follow‐up and prognostic factors in dogs with PDH treated with trilostane were reported . Median follow‐up in 85 patients was 852 days with a 1‐year survival of 70% and a 3‐year survival of 29%.…”
mentioning
confidence: 99%
“…Median follow‐up in 85 patients was 852 days with a 1‐year survival of 70% and a 3‐year survival of 29%. Age and serum phosphate concentrations were found to be prognosticators for survival time . The introduction of trilostane as a treatment option may have contributed to an increase in pituitary gland size of the patients that were referred for hypophysectomy over the past decade, possibly also influencing the outcome of these patients.…”
mentioning
confidence: 99%
“…Ketoconazole is likely to have several cortisol synthesis-inhibiting mechanisms of action, including general inhibition of P450 enzymes and 11β hydroxylase (Loose et al, 1983;Loli et al, 1986). However, its efficacy is underwhelming, especially in light of better medical options being available, despite some reports suggesting it to be relatively effective, with improvement of HAC-associated clinical signs in 43 of 48 dogs and survival times comparable to mitotane and trilostane (median survival 810 vs 622 to 852 days, respectively) (Barker et al, 2005;Lien and Huang, 2008;Fracassi et al, 2014). Idiosyncratic ketoconazole-induced hepato-and other toxicity appear to be rare, but therapy is commonly associated with gastrointestinal upset (Lien and Huang, 2008;Mayer et al, 2008).…”
Section: Medical Managementmentioning
confidence: 99%
“…Older age and heavier weight are negative prognostic factors reported in several studies; higher one hour post-ACTH serum cortisol, weakness at presentation, hyperphosphataemia and severity of clinical signs have also been reported as negative prognostic indicators (Kintzer and Peterson, 1991;Barker et al, 2005;Clemente et al, 2007;Arenas et al, 2014;Fracassi et al, 2014). There are a small number of studies reporting use of alternative drugs to manage HAC.…”
Section: Medical Managementmentioning
confidence: 99%